2019
DOI: 10.1097/dcr.0000000000001325
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Total Neoadjuvant Therapy Followed by Radical Resection Versus Conventional Therapy for Locally Advanced Rectal Cancer

Abstract: BACKGROUND: Definitive surgery with total mesorectal excision is the mainstay of treatment for locally advanced rectal cancer. Multimodality therapy improves long-term survival. Current standards advise neoadjuvant chemoradiation followed by radical surgery and adjuvant chemotherapy. Nationally, compliance with adjuvant chemotherapy is only 32%. New research evaluates the effectiveness of total neoadjuvant therapy: complete chemotherapy and chemoradiation before surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…13 Additionally, a cost-effectiveness analysis in terms of disease-free life-years, incremental cost-effectiveness ratio and net monetary benefit of TNT versus standard LCCRT by Wright et al concluded the former was more cost-effective and a sensitivity analysis showed that a low rate of adjuvant chemotherapy administration played a key role in decreasing the cost-effectiveness in the latter. 14 Like the RAPIDO cohort, we found no significant difference in acute toxicity between both groups, although there was an increased incidence of ≥grade 3 events in the TNT group as expected as a result of more intensive treatment. However, high doses per fraction in SCRT may result in late toxicity so long-term follow up of this study population will be necessary.…”
Section: Discussionsupporting
confidence: 56%
“…13 Additionally, a cost-effectiveness analysis in terms of disease-free life-years, incremental cost-effectiveness ratio and net monetary benefit of TNT versus standard LCCRT by Wright et al concluded the former was more cost-effective and a sensitivity analysis showed that a low rate of adjuvant chemotherapy administration played a key role in decreasing the cost-effectiveness in the latter. 14 Like the RAPIDO cohort, we found no significant difference in acute toxicity between both groups, although there was an increased incidence of ≥grade 3 events in the TNT group as expected as a result of more intensive treatment. However, high doses per fraction in SCRT may result in late toxicity so long-term follow up of this study population will be necessary.…”
Section: Discussionsupporting
confidence: 56%
“…Previous work has demonstrated that total neoadjuvant therapy is more cost-effective than nCRT and surgery followed by adjuvant chemotherapy; however, this current model included patients with both adjuvant and neoadjuvant chemotherapy, and comparing only total neoadjuvant therapy BU and SU patients could alter results. 26 Finally, in this study, patients who had a complete clinical response were not considered for a watch-and-wait approach; rather, all received surgery. Incorporating a watch-and-wait strategy would be a useful area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…This approach offers early systemic control, helps avoid postoperative chemotherapy-related toxicity and improves completion rates by delivering the therapy before surgery when the patients are most fit and compliant 41,42 . Studies show that TNT has similar oncological outcomes to postoperative chemotherapy, facilitates delivery of planned systemic therapy and nonoperative treatment strategies aimed at organ preservation, and is more cost-effective 36,42,43 .…”
Section: [H1] Neoadjuvant Treatmentmentioning
confidence: 99%